Information System Technology Using Web For Online Absence System Implementation - Kurniawan, Heri; Mayasari, Nova; Aufa, Bilal (Cattleya Darmaya Fortuna, 2024)
In today's digital era, the need for an efficient and easily accessible attendance system is increasingly important, especially in educational and organizational environments. Traditional attendance systems often require manual recording which is time-consuming and prone to errors. Therefore, information technology-based solutions that utilize web platforms can provide a more effective and modern way of managing attendance. This paper aims to describe the implementation of a web-based online attendance system, identify the advantages of this technology, and evaluate its functionality and effectiveness in managing attendance data in real-time. The online attendance system is developed using modern web technologies, including HTML, CSS, JavaScript, and backend frameworks such as PHP or Node.js, as well as relational databases such as MySQL. This system allows users to take attendance online through a web interface, with data automatically stored and managed on the server. The implementation process includes developing a user interface, creating an authentication and authorization system, and integrating with a database for data storage and analysis. The developed web-based attendance system provides easy access for users to take attendance from any location with an internet connection. Key features include user authentication, real-time attendance recording, and statistical reports that can be accessed directly through a web dashboard. The system also provides automatic notification to users and administrators regarding absence status and violations. The implementation of a web-based online attendance system has proven to be an effective and efficient solution for attendance management. By utilizing web technology, organizations can optimize the attendance process, reduce errors, and increase data accessibility. Further development and enhancement of the system are needed to overcome existing challenges and ensure the long-term success of the system.